IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA PROGRAM SEKOLAH PENGGERAK DI TAMAN KANAK-KANAK - Hasanah, Lathipah (Journal of Early Childhood Education (JECE), 2023)
This research aims to describe the implementation of the Pancasila Student Profile (P5) strengthening project in the driving school program. This research uses qualitative methods with a case study type. The data collection techniques used were interviews, observations, and documentation. In this study, researchers interviewed five driving school principals and 10 teachers at driving schools. Researchers also observed the implementation of the Pancasila Student Profile strengthening project activities in five driving schools. The five driving schools that were the data sources for this research are: Marsudirini Kindergarten, Amanah Bangsa Kindergarten, Assuryaniyah Islamic Kindergarten, Prima Sakinah Kindergarten, and An Nur Islamic Kindergarten. The results of this study indicate that the implementation of the Pancasila Student Profile (P5) strengthening project in the driving school program emphasizes the importance of holistic competency development. Six competency dimensions include (a) having faith and piety in God Almighty and having noble character, (b) global diversity, (c) mutual cooperation, (d) independence, (e) critical reasoning, and (6) creativity. Meanwhile, the process of internalizing the Pancasila Student Profile character in the project approach carried out by teachers in the driving school program goes through several stages related to teacher skills in: (a) acquiring knowledge, (b) improving skills, (c) developing dispositions, (4) developing feelings, (5) stimulating social-emotional abilities, and (6) fostering children's character.